2018
DOI: 10.1177/0143034318810318
|View full text |Cite|
|
Sign up to set email alerts
|

Trajectories of academic burnout in adolescents after the Wenchuan earthquake: A latent growth mixture model analysis

Abstract: Changes in academic burnout in adolescents have attracted much research attention; however, most studies assume that adolescent academic burnout is characterized by overall homogenous change and overlook the heterogeneity of burnout change. To address this issue, this study examined distinct latent trajectories of academic burnout in adolescents following the Wenchuan earthquake, China. Adolescents were surveyed at 1 (T1), 1.5 (T2), 2 (T3), and 2.5 years (T4) after the earthquake. Self-reported questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Invasive and active rumination have been shown to impact post-traumatic recovery and growth both positively and negatively, and thus should be investigated individually. Individual internal and environmental factors should also be taken in to consideration ( Shallcross et al, 2016 ; Zhou et al, 2019b ). For example, individual resilience, emotional regulation, and external social support are protective factors for an SV’s healing from psychological trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive and active rumination have been shown to impact post-traumatic recovery and growth both positively and negatively, and thus should be investigated individually. Individual internal and environmental factors should also be taken in to consideration ( Shallcross et al, 2016 ; Zhou et al, 2019b ). For example, individual resilience, emotional regulation, and external social support are protective factors for an SV’s healing from psychological trauma.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of coping with these problems, adolescents may suffer from a lack of physical and mental resources. Engaging in learning activities (such as attending lectures and doing homework) requires adequate physical and mental resources; students with PTSD symptoms might lack the physical and mental resources required to meet academic demands, thus resulting in a sense of academic boredom (Zhou et al, 2017b(Zhou et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) is one of the most common negative psychological reactions to the pandemic ( Imran et al, 2020 ; Yue et al, 2020 ; Zhen and Zhou, 2021 ). PTSD not only leads to cognitive and emotional problems ( Dekel et al, 2013 ; Xu et al, 2017 ), but also causes academic difficulties in adolescents ( Zhou et al, 2017b , 2018 ). Thus, the relation between PTSD and academic difficulties should be concerned in the context of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies identified trajectories with decreasing SBO levels. Zhou et al (2019) found that 10.7% of their sample of lower secondary students showed a pattern of decreasing burnout. Meanwhile, Salmela‐Aro and Upadyaya (2014) found that 8% of adolescents from lower to upper secondary had decreasing SBO, while 94% of upper secondary students showed slightly decreasing, moderate levels of SBO.…”
Section: Resultsmentioning
confidence: 99%